Respuesta :

Answer:

(3,1)

Step-by-step explanation:

5x + 3y = 18

2x + 3y = 9

So we can use elimination here to solve this system of equations by multiplying the second equation by -1

Now we have:

5x + 3y = 18

-2x - 3y = -9

Now we add straight down and combine like terms

The y terms cancel and we are left with 3x = 9, dividing both side by 3 we get x = 3

Now we can plug this x value into one of the original equations to solve for our y value

I will use the first equation: 5(3) + 3y = 18 → condensing the terms we get  15 + 3y = 18 → subtracting the 15 from both sides we get 3y = 3 → dividing both sides by 3 we get y = 1

The solution to this system of equations is (3, 1)

ACCESS MORE